Detection of Antibiotic Residues in Beef and Beef Liver in Gorontalo City - Taha, Siswatiana Rahim; Datau, Fahria; Rokhayati, Umbang Arif; Unggango, Yenti (TERNAK TROPIKA Journal of Tropical Animal Production, 2024)
This study aims to determine the presence of antibiotic residues in beef and beef liver sold at the slaughterhouse (TPH) in Gorontalo City. The total of the samples are 34 samples, there are 20 samples of beef and 14 samples of beef liver in Gorontalo City. Testing of beef and beef liver samples using agar diffusion method. The presence of antibiotic residues can be seen from the formation of an inhibitory zones around the disc paper. The results of the study found that in sampling from the slaughterhouses in Gorontalo City, samples of beef liver from TPH Andalas gave a diameter of inhibitory zones about 11.37 mm. Beef liver samples from Padebuolo TPH gave an inhibitory zones about 8.12 mm, while beef liver samples taken from TPH Moudu gave a diameter of inhibitory zones about 15.39 mm and 10.99 mm. Then the second sample, the samples of beef from TPH Andalas gave a diameter of inhibitory zones about 12.68 mm and 9.95 mm. Beef samples from Padebuolo TPH gave inhibitory zones about 9.12 mm and 12.44 mm, while beef samples taken from TPH Moudu gave a diameter of inhibitory zones about 11.69 mm and 8.42 mm. As for TPH Biau, beef samples gave inhibitory zones about 9.86 mm and 8.11 mm. The results at each time of collecting the samples showed that most of the samples contained antibiotic residues with a weak category with the average diameter about 12.3 mm. The conclusion from the laboratory tests on 26 samples, they are 14 samples of beef and 12 samples of beef liver which were analyzed qualitatively using methanol solution showed that some of the samples were identified as antibotic residues, which were shown by the formation of inhibitory zones in each sample.